Banana diseases and pests: field guide for diagnostics and data collection - Viljoen, Altus; Mahuku, George S.; Massawe, C.; Tendo Ssali, R.; Kimunye, J.N.; Mostert, G.; Ndayihanzamaso, P.; Coyne, Danny L. (2017)
Improvement of banana for smallholder farmers in the Great Lakes Region of Africa This unique project seeks to improve the production and productivity of banana in Tanzania and Uganda, through the development of hybrid banana varieties that are expected to have 30% higher yield compared to the current varieties grown by farmers under the same conditions through improved resistance against key pests and diseases. In particular, the project will strengthen the banana breeding programs in the two countries, towards developing new high-yielding and disease-resistant hybrid banana varieties, primarily focusing on the two most popular cooking bananas in the region: East Africa highland banana (EAHB), also known as Matooke, and on Mchare.